2015
DOI: 10.2147/bctt.s85442
|View full text |Cite
|
Sign up to set email alerts
|

Triple negative breast cancer: an Indian perspective

Abstract: IntroductionBreast cancer is the most common female cancer in the world. Triple negative breast cancer (TNBC) is a recently identified biological variant with aggressive tumor behavior and poor prognosis. Data of hormonal status from the Indian population is scarce due to financial constraints in performing immunohistochemistry evaluation. The present study aims to prospectively analyze receptor status of all breast cancer patients and identify TNBC and compare their clinical profile and short term survival wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 18 publications
(12 reference statements)
2
32
0
Order By: Relevance
“…We found 22% of total breast cancer cases as TNBC which has a similar incidence to that reported in some Indian studies [12,13]. However, many Indian studies have reported higher TNBC prevalence such as 39.8% and 43.5% [5,14]. akur et al [15]…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…We found 22% of total breast cancer cases as TNBC which has a similar incidence to that reported in some Indian studies [12,13]. However, many Indian studies have reported higher TNBC prevalence such as 39.8% and 43.5% [5,14]. akur et al [15]…”
Section: Discussionsupporting
confidence: 82%
“…TNBC contributes to a large proportion of breast cancer deaths despite its small proportion among all breast cancers. Prevalence of TNBC in India is considerably higher compared with Western populations [4,5]. e recent literature reports an exceptionally high frequency of TNBC (73.9%) in Indian premenopausal women below 35 years of age, in the prime of their reproductive life [6].…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer incidence is growing in both developed and less developed countries; however, there are more deaths due to BC in less developed countries [5]. There are many factors responsible for increased mortality due to BC in resource-limited countries like younger age of presentation, more locally advanced BC stage, more triple-negative BC, more aggressive histology and higher grades of the tumor, patients defaulting and not completing whole treatment or total number of chemotherapies due to poverty/toxicities, money problems, and going for alternative methods of medicine like homeopathy [6].…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence of TNBC in India is considerably higher compared with that seen in Western populations as suggested by various meta‐analysis studies . TNBC tumors are significantly larger with majority of patients presenting as locally advanced stage breast cancer which is histologically more aggressive (grade 3) compared to other groups . Survival studies have revealed the fact that two‐third of patients at time of disease presentation are in advanced‐stage which account for the poor overall survival .…”
Section: Methodsmentioning
confidence: 99%